2011
DOI: 10.1137/090777360
|View full text |Cite
|
Sign up to set email alerts
|

Breathing Modes of Long Josephson Junctions with Phase-Shifts

Abstract: Abstract. We consider a spatially inhomogeneous sine-Gordon equation with a time-periodic drive, modeling a microwave driven long Josephson junction with phase-shifts. Under appropriate conditions, Josephson junctions with phase-shifts can have a spatially nonuniform ground state. In recent reports [Phys. Rev. Lett. 98, 117006 (2007), arXiv:0903.1046, it is experimentally shown that a microwave drive can be used to measure the eigenfrequency of a junction's ground state. Such a microwave spectroscopy is based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…When excited, the mode will vibrate, but eventually, it will fade away because of 'radiative' damping, i.e., a damping mechanism due to the excitation of higher harmonics with frequencies in the continuous spectrum. Even more, trapped kink oscillations decay asymptotically at a rate of O(t −1/2 ), see [34]. Here, even though our excitations are non-topological, large-amplitude breathers are close to an intertwining pair of kink and anti-kink.…”
Section: Scattering Of Sg Breathersmentioning
confidence: 75%
“…When excited, the mode will vibrate, but eventually, it will fade away because of 'radiative' damping, i.e., a damping mechanism due to the excitation of higher harmonics with frequencies in the continuous spectrum. Even more, trapped kink oscillations decay asymptotically at a rate of O(t −1/2 ), see [34]. Here, even though our excitations are non-topological, large-amplitude breathers are close to an intertwining pair of kink and anti-kink.…”
Section: Scattering Of Sg Breathersmentioning
confidence: 75%
“…By considering u≃ sin u, the considered system becomes the Sine-Gordon equation. In future work, it will be interesting to investigate the Sine-Gordon model with nonlinear AC/DC drives with different fractional operators to study the solitonic behavior, localized modes in single and in stacked long Josephson junctions with a variety of potentials, parity time symmetry, the nonlinearity/dispersion effects, and evolution of the localized monotonic shocks [67][68][69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%
“…where L is a linear self-adjoint operator (L = L † ) given by the left-hand side of the above system. Applying the Fredholm theorem [32,51], we obtain the solvability condition…”
Section: Driving Frequency Close To Natural Frequency Of the Systemmentioning
confidence: 99%
“…Recently, the localized modes excitation has been studied in 0 − π − 0 long Josephson junctions for single-mode and two mode oscillations [30][31][32][33] by considering an inhomogeneous sine-Gordon equation with a variety of direct and parametric drives. It has been reported that in 0 − π − 0 long Josephson junctions, the amplitudes of the breathing modes decay with time due to radiative damping and emission of high harmonic radiations, which can be re-balanced by applying appropriate external drives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation